ṬAHA HUSAIN'S SKEPTICISM OF JᾹHILĪ POET AND ITS POSITION IN THE QUR'AN: ANALYSIS OF ṬAHA HUSAIN'S THOUGHT IN FĪ AL-SYI'RI AL-JĀHILĪ - Faruq, Umarul; Riyadi, Abdul Kadir (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
Ṭaha Husain has an educational background in Egypt and Paris, so it is not surprising that he sometimes adopts the methods of orientalist scepticism that he admires many while in Paris. However, he still paid attention to Egypt. As the father of literature at this time, he paid attention to popular Arabic literature, namely the poetry jahili, which he later booked, and he named Fī al-Syi'rī al-Jāhilī, which later changed its name to Fī al-Adāb al-Jāhilī. With qualitative methods and data excavation categorized as research libraries, the author tried to reveal how Taha Husain's study of Arabic literature is contained in his work Fī al-Syi'ri al-Jāhilī. This research resulted in the fact that the poem jahili, according to Ṭaha, is no longer authentic. It has been infiltrated by some interests, both personal, tribal fanaticism, politics, and even religion. Even if there is still genuine poetry, then it is very little. This authenticity made Taha refuse and said that this no longer authentic poetry could not be used as a tool to understand the Qur'an. It must be the other way around because the Qur'an is the only original and most reliable Arabic literature.